Kajian Gerakan Zaman Baru: Implikasi Filosofis dan Spiritualitas bagi Gereja-Gereja Mandarin - Sugiarto, Thio Donald (Jurnal Teologi dan Pelayanan Kerusso, 2025)
The New Age Movement has rapidly developed in recent decades, having a significant impact on various aspects of life, including philosophy and spirituality. The uniqueness of this movement lies in its universal nature, allowing its teachings to be embraced across different religions, including Christianity. This has the potential to influence Mandarin-based churches, which strongly maintain their traditions and culture. This research aims to explore the philosophy and spiritual practices of the New Age Movement within the context of Christianity and assess the extent to which its teachings can interact with Christian values. The main focus of the study is to understand how the New Age Movement is accepted and practiced in Mandarin churches that remain steadfast in preserving their cultural identity and traditions. The study uses a qualitative approach with a descriptive analysis, studying literature related to the movement and observing spiritual practices in Mandarin-based churches to understand its influence on the congregation. The findings indicate that although the New Age Movement has the potential to be accepted within a Christian context, there are challenges in maintaining the sanctity of Christian teachings. The syncretism that characterizes this movement allows for adaptation with church traditions, but care must be taken to avoid altering the substance of Christian teachings. This study provides important insights for Mandarin churches to wisely understand and respond to the influence of the New Age Movement, ensuring that the congregation continues to uphold authentic Christian teachings and does not fall into beliefs contrary to the Christian faith.